PERANCANGAN SISTEM APLIKASI BERBASIS MOBILE UNTUK MENGURANGI TINDAKAN ANCAMAN ATAU KEKERASAN PADA PELAJAR (IMPLEMENTASI : SEKOLAH DHARMA PUTRA) - Jansen Wiratama; Hari Santoso (Faculty of Information Technology, Universitas Tarumanagara, 2019)
Student violence is still one of the problems faced by students, parents and school parties. The lack of openness from students and the limitations of parents and school parties in monitoring student activities resulted in violent acts and threats to students are difficult to avoid. To solve these problems, an application system is needed to make students connect with their respective parents and school through their personal smartphones, so they are expected to Reduce the level of violence, especially among students. The application system will be designed to be mobile-based and the design stage will use the RAD (Rapid Application Development) method. A mobile-based application system that will be designed to utilize the panic button feature to provide notification alerts from students to parents and school parties. The resulting location of the notification alert can be monitored directly on the map (maps) that is available precisely using GPS (Global Positioning System). Kekerasan pada pelajar masih menjadi salah satu masalah yang dihadapi oleh para pelajar, orang tua dan pihak sekolah. Kurangnya keterbukaan dari pelajar dan keterbatasan orang tua serta pihak sekolah dalam melakukan pemantauan aktifitas pelajar mengakibatkan tindak kekerasan dan ancaman pada pelajar menjadi sulit untuk dihindari. Untuk menangani permasalahan tersebut, diperlukan sebuah sistem aplikasi yang membuat para pelajart erhubung dengan orang tuanya masing-masing dan pihak sekolah melalui smartphone pribadi para pelajar, orang tua dan pihak sekolah, sehingga diharapkan dapat mengurangi tingkat kekerasan khususnya di kalangan pelajar. Sistem aplikasi yang akan dirancang berbasis mobile dan pada tahap perancangannya akan menggunakan metode RAD (Rapid Application Development). Sistem aplikasi berbasis mobile yang akan dirancang memanfaatkan fitur panic button untuk memberikan alert notification dari siswa ke orang tua dan pihak sekolah. Hasil lokasi dari alert notification tersebut dapat dipantau langsung pada peta (maps) yang tersedia secara presisi menggunakan GPS (Global Positioning System).